Unesco Chairs. Conservation of the cultural heritage and sustainable development - Guardia, Sara Beatriz (2018)
Cultural heritage is a historical legacy that needs to be taken care of and preserved for its creativity, culturaldiversity, and because it is an identity factor. From this perspective, the relationship between UNESCO Chairsand heritage conservation is substantial. Their correspondence is analyzed based on the statutory framework ofprotection approved by UNESCO in 1972, and the adoption of the concept of Outstanding Universal Value(OUV) of the World Heritage. As well as the following conventions, the UNESCO Culture Work Plan for Latin America, the role of Culture, Education and the UNESCO Chairs. And, in particular, the Cultural Heritage ofPeru and its twelve cultural assets and sites inscribed on the UNESCO World Heritage List. In this context, theUNESCO Chair Cultural Heritage and Sustainable Tourism of the USMP, contributes to sustainable developmentfrom the university, at local, regional and national levels.